Adaptation of Assessment Techniques and Procedures of Music Learning Outcomes in The New Normal Era (Jurnal Seni Musik, 2023)
The change in the Covid-19 pandemic era to the new normal era demands changes in the implementation of learning again. In this regard, this study aims to describe and analyze the adaptation of techniques and procedures for assessing learning outcomes carried out by teachers. The research was conducted with a qualitative descriptive method. Data was obtained through observation, interviews, and document study. The process of checking the validity of the data was done by triangulating data sources. The data analysis technique used descriptive analysis with the stages of data reduction, data presentation, and data verification. The study results show that the implementation of assessments in the Covid-19 pandemic era to the new normal era has changed. During the Covid-19 pandemic and the new normal, the knowledge assessment technique used was the same: the written test. However, the assessment procedures and types of test items were different. During the Covid 19 pandemic, the knowledge questions used were in the form of multiple choice, which was done digitally. Meanwhile, during the new normal, multiple-choice questions and essays were used with digital and manual (written) processing procedures. Skills assessment during the Covid-19 pandemic was carried out using a performance assessment whose object of observation was in the form of a video recording which was sent to a digital platform. Meanwhile, during the new normal, project evaluation was carried out to know the process and the results of the work which the procedures were carried out directly.